2022
DOI: 10.3389/fendo.2022.881524
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Neudesin and Glucose Metabolism in Obese and Overweight Children

Abstract: Childhood overweight and obesity are among the major health problems of modern times, especially in Western countries, due to their association with increased cardiovascular and cancer risk in adulthood. Neudesin, a recently discovered peptide secreted mainly in the brain and adipose tissue, is being investigated for its possible activity as a negative regulator of energy expenditure. We conducted a cross-sectional observational preliminary study with the aim of testing the hypothesis that plasma levels of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
2
2
Order By: Relevance
“…Neudesin levels in the blood of adults with a recent diagnosis of type 2 diabetes were greater than those of controls of the same age and body mass index [18]. In contrast to the majority of the earlier publications, in which neudesin serum concentrations are around 30 times greater than in our study [16,7], We found that the amount of neudesin in the blood of fat teens was much lower than that of normal-weight teens [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Neudesin levels in the blood of adults with a recent diagnosis of type 2 diabetes were greater than those of controls of the same age and body mass index [18]. In contrast to the majority of the earlier publications, in which neudesin serum concentrations are around 30 times greater than in our study [16,7], We found that the amount of neudesin in the blood of fat teens was much lower than that of normal-weight teens [19].…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, compared to controls of the same age and BMI, adult patients with newly diagnosed T2DM had higher serum levels of neudesin (14) . However, the detected serum concentrations of neudesin are roughly 30 times greater than those in our paper in the majority of the earlier papers (14 15, 16) It was noted that obese adolescents' plasma levels of neudesin were significantly lower than those of normal-weight adolescents (17) . The release of neudesin into the blood was thought to be a defence mechanism against IR and being overweight (18) .…”
Section: Discussioncontrasting
confidence: 51%
“…Data on the relationship between IGF-1 levels and weight in children are inconsistent. There are studies describing comparable [2], lower [29][30][31][32][33], or higher [3,20,[34][35][36][37][38][39][40][41] IGF-1 levels and higher IGF-2 levels [4] in obese children compared to their normal-weight peers. However, IGF-1 shows a tendency to drop in children with extremely high BMI values [39].…”
Section: Children's Weightmentioning
confidence: 99%